Virtual Reality as an Innovative Tool for Eating Disorders Psychological Treatment - Abdulnaser Fakhrou; Gabriele Avincola; Giorgia Farruggio; Idria Verduzzo; Pasquale Caponnetto (Health Psychology Research)
# Background